Adapting Southeast Asian Best Practices for Sustainable Development in Banyumas Regency - Darmawan Arif; Afwa Ulil; Hongsiwet Sunae; Fitrah Elpeni; Srirejeki Kiky; Miryanti Renny; Yuliantiningsih Aryuni; Pascarina Hanifa (E3S Web of Conferences)
This study explores the adaptation of successful sustainable development practices from Southeast Asia to Banyumas Regency, Indonesia, as local implementation of the Sustainable Development Goals (SDGs) becomes crucial. Banyumas, with its unique socio-economic and environmental challenges, offers an opportunity to test the adaptability of these practices. The research examines Southeast Asian initiatives, focusing on renewable energy adoption, sustainable agriculture, eco-tourism, and community-based natural resource management. Key success factors and innovative approaches are identified through case studies from Singapore, Malaysia, and Thailand, considering geographical and cultural similarities. The study assesses the current state of sustainable development in Banyumas, highlighting local challenges and opportunities. By comparing regional best practices with the specific needs of Banyumas, the study proposes a tailored framework for implementing sustainable strategies. Findings suggest that while direct replication of Southeast Asian practices may be impractical, localisation efforts make adaptation feasible. The study recommends a phased approach, emphasising community engagement, capacity building, and policy alignment. This research contributes to understanding SDG localisation, providing insights for policymakers and development practitioners in Banyumas Regency to enhance the quality of life while preserving natural resources for future generations.